the vertex of the parabola represented by f(x)=x^2-2x+6 has coordinates (1,5). Find the coordinates of the vertex of the parabola defined by g(x)=f(x+3). Explain how you arrived at your answer

Answers

Answer 1
Answer: Plug \ in \ x+3 \ into \ f(x) \ to \ get \ g(x) \n\ g(x) = (x+3)^2-2(x+3)+6 \n\ g(x)= x^2+6x+9 -2x-6+6 \n\ g(x) = x^2+4x+9 \n\ -(b)/(2a) --\ \textgreater \ vertex \n\ \frac {-4}{2} \n\ x \ coordinate = -2, plug \ it \ back \ into \ g(x) \n\ (-2)^2+4(-2)+9 \n\ 4-8 + 9 \n\ y \ coordinate = 5 \n\ \boxed{(-2,5)}

Related Questions

How many sixties are in 244?
Of the 30 girls who tried out for the lacrosse team at Euclid Middle School, 12 were selected. Of the 40 boys who tried outo, 16 were selected. Are the ratios of the number of students on the team to the number of students trying out the same for both boys and girls? How do you know?
A guy-wire is attached to a pole for support. If the angle of elevation to the pole is 67° and the wire is attached to the ground at a point 137 feet from the base of the pole, what is the length of the guy wire (round to 2 decimal places)?. . A) 58.15 feet. . B) 143.40 feet. . C) 148.83 feet. . D) 350.62 feet
Do political maps have legends and scales? and what is something interesting about them?
How do you solve 3(m + 5 + 9m)

0.33 in a fraction simplest

Answers

That's 33/100 and can't be simplified. If you had said that the 3s keep going and never end, then it would have been 1/3. But as written, it's just 33/100.
.33 *  (100)/(100) =  (33)/(100)

and that's the most you can simplify it.

Someone help me please

Answers

Answer:

A. Length= 1.5 inches

width= 2 inches

B. 15

Step-by-step explanation:

seems the question has been answered already 15

What is 1,015/12 as a mixed number and in simplest form?

Answers

it would be 84 and 7/12

Simplify the expression 4-3(2+5v)+7

Answers

4-3(2+5v)+7

= 4-(6+6c)+7
= 4-6-6v+7
= -2-6v+7
= 4-6v
= 2(2-3v) (ans)

F(x)=(3x-1)/(2) find f^(-1)(2)

Answers

Answer:

f^(-1) (2)=(5)/(3)

Step-by-step explanation:

To find the inverse of a function, we must replace y for x and then solve for y.

y=(3x-1)/(2) \nx=(3y-1)/(2) \n2x=3y-1\n3y=2x+1\ny=(2x+1)/(3) \nf^(-1) (x)=(2x+1)/(3)

Now we can substitute x=2 into our inverse function

f^(-1) (2)=(2(2)+1)/(3) \nf^(-1) (2)=(5)/(3)

Write one and two hundred fifty three thousandths in standard form

Answers

1.253
Is the answer to ur question